Proceedings of Sixth International Conference on Soft Computing for Problem Solving SocProS 2016, Volume 1 - Deep, Kusum; Bansal, Jagdish Chand; Das, Kedar Nath.; Lal, Arvind Kumar; Garg, Harish; Nagar, Atulya K.; Pant, Millie; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This two-volume book gathers the proceedings of the Sixth International Conference on Soft Computing for Problem Solving (SocProS 2016), offering a collection of research papers presented during the conference at Thapar University, Patiala, India. Providing a veritable treasure trove for scientists and researchers working in the field of soft computing, it highlights the latest developments in the broad area of "Computational Intelligence" and explores both theoretical and practical aspects using fuzzy logic, artificial neural networks, evolutionary algorithms, swarm intelligence, soft computing, computational intelligence, etc.
Adaptive Scale Factor based Differential Evolution Algorithm -- Adaptive Balance Factor in Particle Swarm Optimization -- Community detection in complex networks: a novel approach based on ant lion optimizer -- Hybrid SOMA: A Tool for Optimizing TMD Parameters -- Fast Convergent Spider Monkey Optimization Algorithm -- Bi-level problem and SMD Assessment Delinquent for Single Impartial Bi-level Optimization -- An Adaptive Firefly Algorithm for Load Balancing in Cloud Computing -- Review on Inertia Weight Strategies for Particle Swarm Optimization -- Hybridized Gravitational Search Algorithms with Real Coded Genetic Algorithms for Integer and Mixed Integer Optimization Problems -- Spider Monkey Optimization Algorithm based on Metropolis principle -- An Analysis of modeling and optimization production cost through fuzzy linear programming problem with symmetric and right angle Triangular fuzzy number -- A New Intuitionistic Fuzzy Entropy of Order-  With Applications in Multiple Attribute Decision Making -- The relationship between intuitionistic fuzzy programming and goal programming -- Implementation of Fuzzy Logic on FORTRAN Coded Free Convection around Vertical Tube -- Availability analysis of the Butter Oil Processing Plant using intuitionistic fuzzy differential equations.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence